A critical discourse analysis of how leading news programs TV Patrol, 24 Oras, and Frontline Pilipinas navigated sinophobic narratives in the coverage of the COVID-19 pandemic, the West Philippine Sea conflict, and Philippine Offshore Gaming Operators during the years 2021, 2023, and 2024 - Basa, Alleia Marie E.; Sulit, Cherady Vivienne C.
Drawing from Fairclough’s Critical Discourse Analysis and Machin and Mayr’s Multimodal Critical Discourse Analysis models, this study aimed to determine how leading news programs, specifically TV Patrol, 24 Oras, and Frontline Pilipinas navigated Sinophobic narratives. The study used a qualitative approach to examine and interpret selected broadcast news segments pertaining to the issues of the COVID-19 pandemic, the West Philippine Sea conflict, and Philippine Offshore Gaming Operators during select peak periods in 2021, 2023, and 2024. Specifically, the researchers coded selected news segments, interviewed producers, and analyzed online comments from viewers. The researchers found that the news outlets did not overtly perpetuate anti-Chinese sentiments. However, Sinophobia was implicitly communicated upon scrutinizing the texts, discourse practices, and sociocultural contexts. Anti-Chinese sentiments were subsumed within the production, distribution, and consumption of the news segments. Despite newsroom efforts to avoid conveying Sinophobic narratives, the viewers’ comments suggested a broadly negative perception of China and Chinese individuals, highlighting a potential gap between newsroom intentions and audience reception.